Sense and avoid in UAS research and applications - Angelov, Plamen P.; ebrary, Inc. (Hoboken, N.J. : Wiley, 2012)
"State-of-the-art in research in this challenging yet crucial and topical field, addressing the challenges associated with sense and avoid systems in UASs/ UAVs in their complexity and entirety. Sense and avoid systems are a key technology in the fastest growing field of aircraft development - unmanned aircraft systems. Sense and Avoid in UAS: Research and Applications addresses the challenges associated with sense and avoid systems in UASs/ UAVs in their complexity and entirety. Encompassing the state-of-the-art in research in this challenging yet crucial and topical field, it isauthored by leading practitioners and researchers from three different continents worldwide working on £multi-million research programmes such as ASTRAEA. Highly original, it fulfils the current gap in the published literature on sense and avoid covering views and analyses from sensing to guidance to human factors to regulatory issues. The authors assume some basic knowledge of aviation navigation and aerodynamics, but address principles rather than complex mathematics. Addresses the challenges associated with sense and avoid systems in UASs/ UAVs in their complexity and entirety Fulfils the current gap in published literature on sense and avoid Covers views and analyses from sensing to guidance to human factors to regulatory issues Authored by leading researchers as well as industry practitioners worldwide"--
pt. 1. Introduction -- pt. 2. Regulatory issues and human factors -- pt. 3. SAA methodologies -- pt. 4. SAA applications.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Airplanes -- Collision avoidance; Drone aircraft -- Control systems; Electronic books